2016
DOI: 10.1111/ssm.12150
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Model of Acceptance: Preservice Teachers Interact With Non‐English‐Speaking Latino Parents Using Culturally Relevant Mathematics and Science Activities at Family Learning Events

Abstract: The following describes a culturally relevant mathematics and science content program implemented by preservice teachers (PSTs) at Family Math/Science Learning Events (FM/SLEs) conducted through two different university programs in south Texas. These experiences are required course activities designed to inform PSTs of the importance of interacting with Latino families' culture and language in after school settings. Data were collected from elementary PSTs attending FMLEs and include interactions recorded duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…While categorizing the studies into themes, I found many commonalities, similarities, and differences between the studies. Four studies, namely Johnson (2011), Grimberg and Gummer (2013); Tolbert (2015); and Ramirez, McCollough, and Diaz (2016) highlighted the benefits of using culturally relevant science pedagogical strategies during either professional development programs or learning events for preservice teachers. The other four studies, Luft et al (1999), Patchen and Cox-Petersen (2008), Laughter and Adams (2012), and Morales-Doyle (2017) were all case studies, where the researchers used culturally relevant science pedagogical strategies and reported positive outcomes in the students and teachers who participated in the studies.…”
Section: Thematic Categorizationmentioning
confidence: 99%
See 2 more Smart Citations
“…While categorizing the studies into themes, I found many commonalities, similarities, and differences between the studies. Four studies, namely Johnson (2011), Grimberg and Gummer (2013); Tolbert (2015); and Ramirez, McCollough, and Diaz (2016) highlighted the benefits of using culturally relevant science pedagogical strategies during either professional development programs or learning events for preservice teachers. The other four studies, Luft et al (1999), Patchen and Cox-Petersen (2008), Laughter and Adams (2012), and Morales-Doyle (2017) were all case studies, where the researchers used culturally relevant science pedagogical strategies and reported positive outcomes in the students and teachers who participated in the studies.…”
Section: Thematic Categorizationmentioning
confidence: 99%
“…The next two studies based on PD programs that I am going to compare are those of Tolbert (2015) and Ramirez et al (2016). Even though both studies were conducted in CULTURALLY RELEVANT SCIENCE TEACHING 9 different parts of the world, there were commonalities.…”
Section: Culturally Relevant Science Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…The next two studies based on PD programs that I am going to compare are those of Tolbert (2015) and Ramirez et al (2016). Even though both studies were conducted in different parts of the world, there were commonalities.…”
Section: Similarities In Research On Pd Programsmentioning
confidence: 99%
“…Culture was determinant when within cultural influence, perception and story problems interplayed with Allen's ability to solve mathematics tasks (e.g., the references to the rocket ship and the use of the piñata). Following the principles of culturally relevant pedagogy, we questioned the linguistic and cultural assumptions [75] we used in the mathematics interventions that could have prevented Allen from performing compensation and inversion tasks.…”
mentioning
confidence: 99%